A inovação nas bibliotecas universitárias públicas do estado de São Paulo no contributo ao desenvolvimento nacional - Silva, Maíra Prado da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
It understands innovation as a determining factor in competitiveness indices and development of countries. The university presents itself as a promoter of innovation before its role in generating knowledge. In this sense, the academic library is firm as an informational supportive environment, basic requirement to foster innovation, and resources used to provide the information are made possible through the services and products offered by academic libraries. The dynamic environment surrounding the university and its information units demand the inclusion of innovative activities to services and products. Thus, the research problem sets in how to understand the public academic libraries in the state of São Paulo are innovating in their products and services, helping to build knowledge to generate innovation. The overall objective of the research is to analyse the services and products generated by university libraries. The research has a qualitative approach of descriptive exploratory character, and was characterized as a multiple case study. The instruments used for data collection are the development of product and services line extension and conducting interviews with representatives of the three state academic library systems. Therefore, the content analysis method, specifically the Categorical Content Analysis technique was applied in order to guide the data collection and data analysis, subsequently allowing inferences regarding the problem of this research. The results demonstrate the existence of innovation in products and services offered by academic libraries. However, the innovation is harnessed over the traditional products and services. It was found that there are few innovative products and information services targeted to assist innovation activities within the university. So also sought to offer products and services that can be offered in support of subsidizing the generation of innovation in universities as well as ...

Compreende-se a inovação como fator determinante nos índices de competitividade e desenvolvimento dos países. A universidade apresenta-se como promotora de inovação diante de seu papel de geradora do conhecimento. Nesse sentido, a biblioteca universitária se firma como um ambiente de apoio informacional, requisito básico para fomentar a inovação, e os recursos utilizados para disponibilizar a informação são viabilizados por meio dos serviços e produtos oferecidos pelas bibliotecas universitárias. O ambiente dinâmico que envolve a universidade e suas unidades de informação demanda a inserção de atividades inovadoras aos serviços e produtos. Dessa maneira, o problema da pesquisa configura-se em entender como as bibliotecas universitárias públicas do estado de São Paulo estão inovando em seus produtos e serviços, auxiliando na construção de conhecimento para a geração de inovação. O objetivo geral da pesquisa consiste em analisar os serviços e produtos gerados pelas bibliotecas universitárias. A pesquisa possui abordagem qualitativa de caráter descritivo exploratório, e caracterizou-se como estudo de casos múltiplos. Os instrumentos utilizados para a coleta de dados consistem no desenvolvimento da linha de extensão de produtos e serviços e na realização de entrevista com os representantes dos sistemas de bibliotecas das três universidades públicas estaduais. Para tanto, o método Análise de conteúdo, mais especificamente a técnica Análise de Conteúdo Categorial foi aplicada visando nortear a coleta de dados e a análise de dados, permitindo posteriormente as inferências em relação a problemática desta pesquisa. Os resultados demonstram a existência de inovação nos produtos e serviços oferecidos pelas bibliotecas universitárias. No entanto, a inovação atrela-se mais aos produtos e serviços tradicionais. Constatou-se que existem poucos produtos e serviços de informação inovadores...
Keywords: Bibliotecas universitárias - São Paulo (Estado); Tecnologia - Serviços de informação; Tecnologia da informação; Inovações tecnologicas; Academic libraries